Polemika wokół „Pułtawy” i „Jagiellonidy”, czyli oświeceniowy spór o kształt eposu - Kwiatkowska, Agnieszka (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2019)
The Polemic around Jagiellonida and Pułtawa: Enlightenment Controversy on The Nature of The Epic Genre In the 18th century the convention of the literary epic underwent radical changes. These were responsible for numerous episodes of discussion in regard to among others, the chronological distance of events described and the nature of the function of fantasy. The most renowned literary critics entered the fray (in Poland among others, Filip Neriusz Golański, Franciszek Ksawery Dmochowski and Ignacy Krasicki). Leading Polish writers in turn, created new epics, fusing traditions of the Antique World with that of innovative literary devices. Critical-literary opinions in regard to particular works can be seen to be part of the broad polemic in respect to this genre convention. Literary reception at the time to these particular works (Pułtawa by Nikodem Muśnicki and Jagiellonida by Dyzma Bończa Tomaszewski) provides a critical portrayal and undertakes the most vital issues concerning the genre per se.
The Polemic around Jagiellonida and Pułtawa: Enlightenment Controversy on The Nature of The Epic Genre